Peningkatan Berpikir Kritis Dan Kecerdasan Emosional Siswa Melalui Integrasi STEAM Dalam Pembelajaran Berbasis Proyek - Khansa Daiyah Rosidah; Fitri Yanti (JURNAL KEILMUAN TEKNOLOGI DAN PENDIDIKAN TERPADU, 2026)
The Industrial Revolution 4.0 era demands the development of students' critical thinking skills and emotional intelligence, especially in informatics learning. This study aims to analyze the effectiveness of Project-Based Learning (PjBL) integrated with Science, Technology, Engineering, Arts, and Mathematics (STEAM) in developing these two competencies simultaneously in grade X students of SMA Negeri 2 Bungo. Using a true experimental design, the study involved 68 students who were divided into experimental and control groups. Data was collected through a validated and reliable questionnaire, then analyzed using the Independent Sample t-Test and MANOVA tests. The results of the analysis showed that STEAM-based PjBL had a partial significant effect on the improvement of students' critical thinking skills (p=0.036) and emotional intelligence (p=0.017). Furthermore, the MANOVA test confirmed that STEAM-based PjBL simultaneously had a significant influence on both competencies (F=4.324; p=0.008). These findings indicate that the integration of PjBL and STEAM is an effective learning strategy in developing the cognitive and social-emotional competencies that are crucial for students in facing the challenges of the 21st century.   Keywords: Project-Based Learning; STEAM; Critical Thinking; Emotional Intelligence; Informatics Learning.